An Injection Molding Process in Plastic- A review (International Journal of Scientific Research in Science and Technology, 2025)
A growing sector of the plastics industry, the term “plastic” encompasses a broad range of materials. In addition, each has its own special properties and variations when it comes to properties such as hardness, heat tolerance, and resiliency. Each of them is made of organic condensation or addition polymers and can be made into fibers, films, or objects. Plastic injection molding is the most common process used to produce plastic parts. The process of plastic injection molding is fast, meant to produce large quantities of the same plastic product in a short time span. Now a days, the materials used are for instance thermoplastic, thermoset, elastomer, and/or metal(s). High-performance plastics that can withstand high temperatures are replacing the metals that are traditionally used in plastic manufacturing.